Analisis Penerimaan Sistem Open Public Access Catalog (OPAC) di Perpustakaan Universitas Medan Area Menggunakan Technology Acceptance Model (TAM) - Rahayu, Sri; Sayekti, Retno (Jurnal Teknologi Sistem Informasi dan Aplikasi, 2023)
The Online Public Access Catalogue (OPAC) serves as a key indicator of a library's quality and effectiveness. When it comes to OPAC's information retrieval capabilities, they can make it simpler and quicker to track out relevant data. However, in practice, OPACs and other retrieval systems frequently have problems or erroneous collections. Scientists are interested in OPAC usage because of this. Tthis study intends to gauge patron impressions of the Open Public Access Catalogue (OPAC) system in the Medan Area Library. 50 respondents from Medan Area University served as the study's sample of research participants. In this study, tests are conducted utilising validity tests, reliability testing, and descriptive data analysis. Descriptive quantitative research methodologies are also used. The results showed that the ease of use of the OPAC system had a positive impact on perceptions of the usefulness of the OPAC system and attitudes towards OPAC use.  This shows that if OPAC users feel that this system is easy to use, then bringing benefits to students will then affect acceptance of the OPAC system. Students will tend to continue to use the OPAC system to meet their needs effectively.  The user's attitude towards OPAC has a positive impact on the user's willingness to use OPAC.  In addition, the findings show that behavioral intention positively influences actual OPAC use.  The use of web-based OPAC is mandatory for Medan Area University students, so that it affects the actual use of the OPAC system, this is indicated by the frequency of visits to the Medan Area University library website.  It was concluded that the OPAC system was acceptable to Medan Area University library users.